Overview: The history and pediatric perspectives of severe acute respiratory syndromes: Novel or just like SARS. Issue 7 (1st June 2020) - Hon, Kam Lun; Leung, Karen Ka Yan; Leung, Alexander K. C.; Sridhar, Siddharth; Qian, Suyun; Lee, So Lun; Colin, Andrew A.
Abstract: Many respiratory viral infections such as influenza and measles result in severe acute respiratory symptoms and epidemics. In the spring of 2003, an epidemic of coronavirus pneumonia spread from Guangzhou to Hong Kong and subsequently to the rest of the world. The WHO coined the acronym SARS (severe acute respiratory syndrome) and subsequently the causative virus as SARS‐CoV. In the summer of 2012, epidemic of pneumonia occurred again in Saudi Arabia which was subsequently found to be caused by another novel coronavirus. WHO coined the term MERS (Middle East respiratory syndrome) to denote the Middle East origin of the novel virus (MERS‐CoV). In the winter of 2019, another outbreak of pneumonia occurred in Wuhan, China which rapidly spread globally. Yet another novel coronavirus was identified as the culprit and has been named SARS‐CoV‐2 due to its similarities with SARS‐CoV, and the disease as coronavirus disease‐2019. This overview aims to compare and contrast the similarities and differences of these three major episodes of coronavirus outbreak, and conclude that they are essentially the same viral respiratory syndromes caused by similar strains of coronavirus with different names. Coronaviruses have caused major epidemics and outbreaks worldwide in the last two decades. From an epidemiological perspective, they are remarkably similar in the mode of spread by droplets. Special focus is placed on the pediatric aspects, which carry less morbidity and mortality in all three entities.